Solid phase transformation effects on stress and strain in the thick plate EH40 welded butt joint. (January 2023) - Wu, Ruolin; Huang, Yu; Rong, Youmin; Xu, Jiajun; Chen, Quan
Highlights: 1. A material constitutive model considering complete solid phase transformation was proposed. 2. The stress gradient at the junction of HAZ and BM due to the solid phase transformation was up to 1299 MPa. 3. The FZ and HAZ of the plastic strain considering solid phase transformation were more easily observed. 4. The martensitic transformation was the main reason for the obvious difference of stress and strain distribution and the evolution mechanism. Abstract: To accurately predict welding-induced residual stress and strain of high strength steel thick plate EH40 butt joint in single-pass full penetration laser welding, a complete solid phase transformation model according to the actual weld microstructure was proposed through material constitutive development. At the same time, the Case 1 considering the traditional thermo-elastoplastic were used as comparative study. The simulation calculation results and experimental results of each phase content were compared and verified. The stress and strain distribution of welded joints and the evolution mechanism of nodes in three zone including fusion zone, heat-affected zone and base metal were deeply studied and compared. The results indicated that the solid phase transformation had an obvious effect on the peak and distribution of longitudinal, transverse, normal and equivalent residual stress, as well as the stress gradient at the junction of heat-affected zone and BM. It increased the peak value of longitudinal residual compressive stress from –103 MPa to –768 MPa, with an increase of 645.6%. The stress gradient at the junction of heat-affected zone and base metal was up to 1299 MPa. The state distribution of longitudinal and transverse stress in the weld and its vicinity were completely opposite to the Case 1. The peak value of transverse plastic compressive strain increased from –0.059 to –0.111, with an increase of 88.1%. The fusion zone and heat-affected zone of the plastic strain in welded joints were more easily observed. It was found that martensitic transformation was the main reason for the obvious difference of stress and strain distribution and the evolution mechanism of stress and strain in the later stage of cooling stage.